2022
DOI: 10.1177/02692163221124033
|View full text |Cite
|
Sign up to set email alerts
|

A thematic analysis of hospital medical records of patients with advanced illness experiencing incarceration in the last 3 months of life

Abstract: Background: The constraining prison culture is not, for the most part, conducive to the provision of palliative care for people in prison. Aim: This study aimed to explore patterns of palliative and end-of-life care provision for hospitalised prison patients. Design: A retrospective qualitative review of hospital medical records to explore the quality of end-of-life care provision for patients experiencing incarceration who died within hospital. Qualitative inductive analysis of record extracts of each patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…5 Although standards exist to limit the use of restraints, across Australia and internationally, reports of prisoner patients dying while shackled to their beds still materialise. [6][7][8][9][10][11][12][13][14] In 2011, following the escape of three prisoners under hospital escort in South Australia, the practice of cuffing prisoners' legs together and to their beds was implemented in settings deemed non-secure, such as hospitals. 10 Subsequently, the independent Ombudsman received multiple complaints, including cases of prisoners being restrained for excessive periods of time.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…5 Although standards exist to limit the use of restraints, across Australia and internationally, reports of prisoner patients dying while shackled to their beds still materialise. [6][7][8][9][10][11][12][13][14] In 2011, following the escape of three prisoners under hospital escort in South Australia, the practice of cuffing prisoners' legs together and to their beds was implemented in settings deemed non-secure, such as hospitals. 10 Subsequently, the independent Ombudsman received multiple complaints, including cases of prisoners being restrained for excessive periods of time.…”
mentioning
confidence: 99%
“…A consecutive sample of male prisoner patients who died in an Australian metropolitan hospital between 2009 and 2019 revealed that shackles were commonly used for patients who were transferred from the secure hospital-based prison ward to the palliative care unit. 14 Here, the palliative care teams expressed concerns about patients being shackled during their final weeks and days of life and that the shackles caused pain and distress to the patients. In this cohort, medical staff report that requests for removal of the shackles were not infrequently declined due to concerns about the patient's security rating and the belief that the shackles did not interfere with medical treatment.…”
mentioning
confidence: 99%
See 2 more Smart Citations